Ancient Chinese Poem “The Song of Bride”: Features of Translation by A.A. Shtukin - Zhiqiang Liu; Yingyin Feng (Научный диалог)
The translation of A.A. Shtukin’s poem “The Song of the Bride”, which is part of the collection of ancient Chinese hymns and songs “Shijing”, is being considered. The relevance of the study is determined by the interest of Chinese researchers in the quality of translations of Chinese poetry into European languages, particularly Russian. There is noted interest from both Chinese and Russian researchers in the translation of the book “Shijing”, as it varies depending on the perception of foreign cultures. The features of A.A. Shtukin’s translation of the poem “The Song of the Bride” are highlighted in terms of the images he created and the linguistic specifics. It is pointed out that Shtukin’s translation of the poems from “Shijing” is recognized as one of the best. The analysis of the translation revealed the following characteristics: the preservation of the original work’s color through botanical metaphors, sound, and structural organization of the text. Some shortcomings in conveying the atmosphere of ancient Chinese lyricism from the perspective of native Chinese speakers who also speak Russian were also identified; the translation differs from the original in that it insufficiently conveys the atmosphere of ancient Chinese lyricism, which can be easily explained by the differences in worldviews among speakers of different languages.